A job crafting measure: psychometric properties of the Polish version of the Job Crafting Scale - Anna Rogala; Roman Cieślak (Nofer Institute of Occupational Medicine, 2019)
Background The interest among researchers and practitioners in job crafting has been growing for the last dozen of years. Job crafting refers to behaviors that employees engage in to align aspects of their jobs with their own skills and needs. The aim of this paper was to analyze psychometric properties of the Polish version of a job crafting measure - the Job Crafting Scale (JCS). Material and Methods The original JCS consists of 21 items and has 4 subscales: Increasing Structural Job Resources , Increasing Social Job Resources , Increasing Challenging Job Demands , and Decreasing Hindering Job Demands . Confirmatory factor analysis, internal consistency analysis, theoretical validity analysis and test-retest stability analysis were carried out among 249 white collar workers who use information and communication technology (ICT) in their daily work. Multigroup confirmatory factor analysis and invariance test were carried out among 228 white collar workers using ICT and additionally working in a team for most of the week. Results The Polish version of the JCS displays satisfactory internal consistency, theoretical validity, and test-retest stability. The results of the confirmatory factor analysis showed a 4-dimensional structure of the JCS. Four items were excluded from the Polish version of the JCS because of low factor loadings. The results of invariance test showed that factor loadings were invariant across groups. Conclusions The Polish version of the JCS consists of 17 items and - like the original scale - has 4 subscales. Additional studies are recommended to confirm the internal structure of the JCS and measurement invariance across different occupational groups. Med Pr. 2019;70(4):445-57